Cuidados paliativos ao paciente com câncer: atuação de fisioterapeutas no âmbito hospitalar - Costa, Emilie de Oliveira (2017)
Introduction: Palliative care is an approach performed by a multidisciplinary team to improve the quality of life of patients with cancer and their family, having as priority the control of pain and psychic, social and spiritual symptoms. This dissertation is composed of two articles: the first, theoretical; it is entitled: Palliative Care and oncology: a bibliometric study. Objective: To analyze the national and the international scientific production published in journals online about palliative care and oncology, in the period from 2007 to 2016. Method: It is regarded as a bibliometric study consisting of 80 articles published in the period from 2007 to 2016, available in LILACS and MEDLINE and, virtual library, SciELO. Results: There was a greater concentration of securities in international journals, in the year 2013, with partners of the United States in the English language. The largest number of publications was produced by researchers with specialist, in the form of original article and with cancer patients under Palliative Care. Conclusion: The results obtained point to the relevance of palliative care in care to cancer patients and for the need of new scientific research relating to the topic. Introduction: The cancer patient in palliative care receives assistance from team composed by professionals from different areas, among which stands out the physiotherapist, which benefits those patients involved in the management of pain, stress, psychophysical on prevention of complications osteomyoarticular lesions, pulmonary, neurological, among others. Objective: To investigate the role of physiotherapists in the promotion of palliative care to cancer patients treated at a hospital institution. Method: A qualitative study conducted in a hospital institution of philanthropic organizations in João Pessoa, PB, with nine physical therapists, through interviews. The data were collected in the period from September to November 2016 and analyzed by means of content analysis technique. Results: From the empirical material emerged four thematic categories: Understanding of physical therapists about palliative care; the relationship of the physiotherapist with the patient in the hospital context; actions of physiotherapists to cancer patients under hospice care; the importance of assisting the patient in palliative care. Conclusion: The physiotherapists demonstrated an understanding about the importance of palliative care to cancer patients and their families, acting as the needs presented. The study presents a contribution to the professional knowledge of the physical therapist.